The Case of onions in Senegal: Improving information and access to technology - Bouët, Antoine (International Food Policy Research Institute, 2017)
AGRODEP is a Modeling Consortium of African researchers living and working in Africa with research interests ranging from economic modeling to regional integration and development to climate change, gender, poverty, and inequality. There are currently 183 members from 27 countries; our members work at top research institutions and universities in their own countries as well as various government agencies and non-profit organizations.